Conceptualizing cyber policy through complexity theory. Issue 2 (4th May 2019) - Brantly, Aaron F.
ABSTRACT: Complexity is a consistent feature of cyberspace. It is resident within the technical, logical and human layers across which socio-technical structures leverage cyberspace. Yet the development of policy often approaches the complex nature of cyberspace through reductionism. This paper argues, using two case examples from cryptography that to develop good policies and laws for cyberspace requires an embrace of a new theoretical framework, that is, complexity theory.